Preserving the Jawi script in Aceh: Assessing literacy, cultural heritage, and modern paradigm challenges - Allif Syahputra Bania; Bachtiar Akob (Universitas Syiah Kuala, 2025)
The use of Jawi, or the Arabic script that uses the Malay language, in the archipelago is gradually declining due to a paradigm shift. Increased Latin script use has diminished the Jawi script literacy, resulting in its perception as inferior. Research on this script as a cultural heritage in the province of Aceh, Indonesia, well-known as the Veranda of Mecca, is necessary, in line with the mandate of the National Education System Law, Qanun No. 11 of 2014 concerning the Implementation of Education, and the UUPA of 2016. This study aimed to explore the understanding of the Jawi script. It employed a descriptive-qualitative approach and the instruments used were a set of test questions and questionnaires. The samples were 100 randomly selected respondents from Langsa City, Aceh. The findings showed that 63 respondents successfully understood the conversion from the Jawi to Latin script, while only 22 could understand the conversion from Latin to the Jawi script. The results further indicated that the majority supported teaching the Jawi script in educational institutions as a means of preserving the cultural heritage of the Acehnese people. Furthermore, the participants ability to read the Jawi script was significantly better than their ability to write it. Hence, this study provides information on the Acehnese linguistic capabilities related to the Jawi script preservation, focusing on its maintenance, use, and literacy role in multilingual contexts. It contributes to the understanding of traditional writing system transmission and perception, enhancing our understanding of language practices in post-colonial societies.